1969
DOI: 10.1901/jeab.1969.12-301
|View full text |Cite
|
Sign up to set email alerts
|

FIXED‐INTERVAL SCHEDULES OF ELECTRIC SHOCK PRESENTATION: EXTINCTION AND RECOVERY OF PERFORMANCE UNDER DIFFERENT SHOCK INTENSITIES AND FIXED‐INTERVAL DURATIONS1

Abstract: In squirrel monkeys responding under a schedule in which responding postponed the delivery of electric shock, the presentation of response-dependent shock under a fixed-interval (FI) schedule increased the rate of responding. When the schedule of shock-postponement was eliminated, so that the only shocks delivered were those produced by responses under the FI schedule, a pattern of positively accelerated responding developed and was maintained over an extended period. When responses did not produce shocks (ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
61
1

Year Published

1969
1969
1990
1990

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 22 publications
9
61
1
Order By: Relevance
“…When US presentations in extinction retard the rate of response cessation relative to that rate obtained with CS-alone extinction, as has been demonstrated most powerfully for avoidance and escape responses (Coulson, Coulson, & Gardner, 1970;Fowler, 1971;Kelleher, Riddle, & Cook, 1963;McKearney, 1969;Stretch, Orloff, & Dalrymple, 1968) but also for conditioned suppression (Ayres & DeCosta, 1971) and leverpressing (Rescorla & Skucy, 1969) in rats, an explanation in terms of the adventitious temporal contiguity of response and reinforcement (Skinner, 1948) is probably most common. Other investigators have emphasized the discriminative properties of reinforcement (Rescorla & Skucy, 1969;Uhl, 1973;Zeiler, 1968).…”
mentioning
confidence: 95%
“…When US presentations in extinction retard the rate of response cessation relative to that rate obtained with CS-alone extinction, as has been demonstrated most powerfully for avoidance and escape responses (Coulson, Coulson, & Gardner, 1970;Fowler, 1971;Kelleher, Riddle, & Cook, 1963;McKearney, 1969;Stretch, Orloff, & Dalrymple, 1968) but also for conditioned suppression (Ayres & DeCosta, 1971) and leverpressing (Rescorla & Skucy, 1969) in rats, an explanation in terms of the adventitious temporal contiguity of response and reinforcement (Skinner, 1948) is probably most common. Other investigators have emphasized the discriminative properties of reinforcement (Rescorla & Skucy, 1969;Uhl, 1973;Zeiler, 1968).…”
mentioning
confidence: 95%
“…Following response acquisition under responsecontingent schedules of food presentation (e.g., Kelleher & Morse, 1968), shock postponement (e.g., McKearney, 1969), or response induction by periodic response-independent shock (e.g., Morse, Mead, & Kelleher, 1967; see Hutchinson, 1977, for a review), lever pressing of squirrel monkeys can be maintained by shock presentation under interval schedules, which present shock following the first response after a specified temporal interval (see Morse & Kelleher, 1977, for a review). But when shock is delivered under ratio schedules, that is, following a specified number of responses, pressing typically is suppressed, even when the number of responses per shock is matched to a preceding condition in which responding was maintained under an interval schedule (Branch & Dworkin, 1981).…”
mentioning
confidence: 99%
“…The superirnposition of response-contingent shock has led to a decrease in response rate when every response was punished (PoweIl & Morris, 1969) and when additional shocks were programmed on fixed-ratio (FR) schedules (Sandler, Davidson, & Holzschuh, 1966; Mclntire et al, 1968), but to an increase in responding when programmed on fixed-interval (FI) schedules (McKearney, 1969).higher shock rate prevailing in this component of the schedule: high shock rate may lead to a decrease in responding but low shock rate to an increase. Using rats, Mclntire et al (1968) found that a FR schedule of response-contingent shock led to a decrease in responding of an avoidance baseline whereas the same rate of noncontingent shock increased responding.…”
mentioning
confidence: 99%
“…The superirnposition of response-contingent shock has led to a decrease in response rate when every response was punished (PoweIl & Morris, 1969) and when additional shocks were programmed on fixed-ratio (FR) schedules (Sandler, Davidson, & Holzschuh, 1966; Mclntire et al, 1968), but to an increase in responding when programmed on fixed-interval (FI) schedules (McKearney, 1969).…”
mentioning
confidence: 99%
See 1 more Smart Citation